Diagnosis and management of a maxillary lateral incisor exhibiting dens invaginatus and dens evaginatus. (24th January 2014) - Akers, Harry Francis; Henderson, Carolyn Mary; Foley, Michael Anthony
Abstract This case report, involving an indigenous Australian, presents the diagnosis and non‐surgical endodontic management of a 22 with developmental abnormalities. They include a dens evaginatus and a dens invaginatus that extends to an apical burst in a second truncated root. Cone‐beam computed tomography and endodontic microscopy were not available to the clinician. This case report focuses on ambiguities appearing in the literature relating to classification and terminology associated with the abovementioned developmental anomalies. It also demonstrates the need to methodically collect and cautiously interpret available information before initiating endodontic intervention. Axial inclination, distance perception, internal demarcation and spatial awareness, together with an understanding of dental anatomy, embryology and histology and associated physiology and pathology, allowed the clinician to accurately predict the point, the angle and the depth of coronal access. Sensibility of the dentino‐pulpal complex was maintained. Critical thinking, experience, innovation, problem‐solving and established principles can compensate for inaccessible technologies.